Treatment of Hydrothermal-Liquefaction Wastewater with Crossflow UF for Oil and Particle Removal - Ali Sayegh; Simon Merkert; Joscha Zimmermann; Harald Horn; Florencia Saravia (Membranes, 2022)
This study aims to evaluate the application of ceramic ultrafiltration membranes in the crossflow mode for the separation of particles and oil in water emulsions (free oil droplets and micelles) from hydrothermal-liquefaction wastewater (HTL-WW) from the hydrothermal liquefaction of municipal sewage sludge. The experiments were carried out using one-channel TiO2 membranes with pore sizes of 30, 10 and 5 nm. The results showed that the highest stable permeability could be achieved with a membrane-pore size of 10 nm, which experienced less fouling, especially through pore blockage, in comparison to the two other pore sizes. Instead of observing an increase in the permeability, the application of a higher feed temperature as well as backwash cycles led to a clear increase in irreversible fouling due to the presence of surfactants in the HTL-WW. Among several physical and chemical cleaning methods, alkaline cleaning at pH 12 proved to be the most efficient in removing fouling and maintaining stable performance on a long-term basis. Ceramic-membrane ultrafiltration can be considered as an adequate first-stage treatment of real HTL wastewater.